2009
DOI: 10.1186/1471-2164-10-26
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory event-based gene set analysis method for exploring global functional changes in heterogeneous genomic data sets

Abstract: Background: Analyzing gene expression data by assessing the significance of pre-defined gene sets, rather than individual genes, has become a main approach in microarray data analysis and this has promisingly derive new biological interpretations of microarray data. However, the detection power of conventional gene list or gene set-based approaches is limited on highly heterogeneous samples, such as tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(51 reference statements)
2
4
0
Order By: Relevance
“…In addition, this study showed that TCD triggered the ER stress-signaling pathway in both Mahlavu and Hep-J5 cells. Our finding is in accordance with several earlier reports that processes involving microtubule-based action and cytoskeletal organization are important biological functions in HCC [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, this study showed that TCD triggered the ER stress-signaling pathway in both Mahlavu and Hep-J5 cells. Our finding is in accordance with several earlier reports that processes involving microtubule-based action and cytoskeletal organization are important biological functions in HCC [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…Using this approach, we found that the cellular assembly and organization through the microtubule functional networks ranked the most significant cellular event in HCC. Our finding is consistent with several earlier reports on expression profiling of HCC, which also suggested the microtubule-based processes and microtubule cytoskeletal organization to be important biological and cellular components in HCC (29,30). In line with our finding, other profiling studies also found the microtubule regulatory gene STMN1 to be commonly upregulated in HCC (31,32).…”
Section: Discussionsupporting
confidence: 83%
“…The whole set of MMT-dependent transcriptomes (both of the up-and downregulated DEGs) was submitted for analysis, which considers all the consistently changed genes and every gene regulation of each sample to avoid the detection limit. 33 Interestingly, a unique Src-centric network that contains most of the MMT-associated DEGs resulted. We further demonstrated the involvement of Src in MMT, as its mRNA expression level was increased in the TGF-b1-stimulated BMDMs from 3 hours onward.…”
Section: Discussionmentioning
confidence: 99%